Anti-Inflammatory and Anti-Metastatic Effects of Herbal Extracts on the HIF-1α/COX-2/MMP-2 axis in Triple-Negative Breast Cancer Cells (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
Triple-negative breast cancer (TNBC) remains a major clinical challenge due to its aggressive nature and lack of targeted therapies. In this study, we investigated the effects of three medicinal plant extracts—Alchemilla smirnovii Juz., Rumex obtusifolius, and Inula helenium—on inflammatory and metastatic markers in MDA-MB-231 human TNBC cells. MDA-MB-231 cells were treated with Alchemilla smirnovii Juz., Rumex obtusifolius, and Inula helenium extracts under CoCl₂- and TNF-α-induced conditions. Protein expression of HIF-1α, COX-2, and MMP-2 was assessed using Western blot and immunocytochemistry. Cytotoxicity was evaluated by MTT assay. Using CoCl₂-induced hypoxia and TNF-α-stimulated inflammation models, we assessed the modulation of the HIF-1α/COX-2/MMP-2 signaling axis. MTT assays confirmed that the extracts, at 0.5 mg/mL, did not exhibit cytotoxicity after 24–72 hours. Western blot analysis revealed that all three extracts significantly downregulated HIF-1α, COX-2, and MMP-2 expression under both basal and stimulated conditions. Notably, A. smirnovii and R. obtusifolius demonstrated the most potent inhibitory effects under TNF-α stimulation, while A. smirnovii and I. helenium were most effective under CoCl₂-induced hypoxia. Immunocytochemistry confirmed these findings, showing decreased fluorescence intensity of COX-2 and MMP-2 and no signs of nuclear condensation, supporting the non-cytotoxic nature of the treatments. These results suggest that the tested plant extracts exert strong anti-inflammatory and anti-metastatic effects without inducing cell death, making them promising candidates for adjunctive therapy in TNBC. Their ability to suppress key pro-tumorigenic markers involved in extracellular matrix remodeling and angiogenesis could help prevent cancer cell invasion and dormancy. This study highlights the therapeutic potential of plant-derived compounds in modulating tumor-associated pathways in breast cancer and supports further investigation of these extracts in combination with conventional chemotherapy.
Keywords: herbs; triple-negative breast cancer; inflammation; metastasis